2016
DOI: 10.1248/cpb.c15-00838
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Solid Dispersion Tablets by a Simple and Manufacturable Wet Granulation Method Using Porous Calcium Silicate

Abstract: The aim of this study was to prepare and evaluate solid dispersion tablets containing a poorly water-soluble drug using porous calcium silicate (PCS) by a wet granulation method. Nifedipine (NIF) was used as the model poorly water-soluble drug. Solid dispersion tablets were prepared with the wet granulation method using ethanol and water by a high-speed mixer granulator. The binder and disintegrant were selected from 7 and 4 candidates, respectively. The dissolution test was conducted using the JP 16 paddle me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Problems can occur if used for oral dosage tablets because FLR is difficult to handle due to its low flowability and high dustiness. Some recent studies have reported that granules including FLR, and poorly water-soluble drugs can be prepared by the wet granulation method to improve the low flowability [ 39 , 40 , 41 ]. Florite ® PS300 (PS300) was developed in response to these problems, and its shape is spherical.…”
Section: Introductionmentioning
confidence: 99%
“…Problems can occur if used for oral dosage tablets because FLR is difficult to handle due to its low flowability and high dustiness. Some recent studies have reported that granules including FLR, and poorly water-soluble drugs can be prepared by the wet granulation method to improve the low flowability [ 39 , 40 , 41 ]. Florite ® PS300 (PS300) was developed in response to these problems, and its shape is spherical.…”
Section: Introductionmentioning
confidence: 99%
“…Porous Calcium Silicate (PCS) and magnesium aluminosilicate (Neusilin ® ) have huge surface areas and are used as solid dispersion carriers to improve the dissolution of poorly water-soluble drugs [10][11][12]. We reported the development of solid dispersion tablets via a simple and easily manufactured wet granulation method using PCS [13,14]. These materials contain silanol groups and metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…PCS is also used as a carrier of solid dispersion for improving the dissolution of poorly water-soluble drugs [38][39][40][41]. We previously reported the development of solid dispersion tablets by the simple and manufacturable wet granulation method using PCS [42,43].…”
Section: Introductionmentioning
confidence: 99%